A National Survey of Health and Safety Knowledge and Beliefs Among Technical Vocational Faculty in Autobody Collision Repair Technology. Issue 7 (July 2020) - Parker, David L.; Bejan, Anca; Marscin, Melissa; Xi, Min
Abstract : Objectives: Career technical education (CTE) programs prepare new generations of technicians in a variety of trades. Even though occupational safety and health (OSH) ought to be included as an essential part of CTE curricula it is frequently absent or inadequately taught. Methods: OSH knowledge and beliefs were assessed in a national sample of 125 secondary and post-secondary faculty in autobody collision repair technology. Results: Over 50% of faculty thought at least 75% of OSH knowledge was learned at school, and 9% felt that safety was primarily learned on the job. Knowledge scores ranged from 22% to 78%. Overall knowledge scores were significantly lower high school than post-secondary instructors (42% vs 50%, P  ⩽ 0.001) and in two categories: hazard recognition (44% vs 54%, P  ⩽ 0.05) and hazard control and shop equipment (30% vs 37%, P  ⩽ 0.05). Conclusions: There are substantial gaps in OSH knowledge among secondary and post-secondary CTE instructors. CTE programs should address these gaps by providing trade-specific safety and health education to their instructors upon hiring.